Translation Techniques of Cultural Words in Chinese Series “The Legend of White Snake” Subtitles - Saeheng, Atjima (Rajapark Journal, 2025)
This article aims to study the translation techniques of cultural words from the subtitles of the Chinese series "The Legend of White Snake." The study found that there are five categories of cultural words in the series: those related to ecology, material, social, religious and belief, linguistic. Eight translation techniques featured in this article are ranked from most to least frequently used as follows: eight translation techniques featured in this article are ranked from most to least frequently used as follows: literal translation (60.73%), paraphrasing (10.55%), mixed literal translation and transliteration (8.91%), transliteration (6.54%), omission (6%), translation by using an idiom of similar meaning but dissimilar form (4.36%), translation by a more general word (2.18%), and using a combination of strategies (0.73%). In summary, literal translation is used for words or idioms present in both the source and target cultures. If the word appears only in the source culture, the translator will translate by using cultural substitution. For unique words without comparable equivalents, a general word will be used. Paraphrasing is used for words with much detail or untranslatable idioms. Transliteration or translation by using an idiom of similar meaning but dissimilar form is used for proper nouns. Omission is used when it doesn’t affect the main meaning. Finally, a combination of strategies is used for complex words.